Removal of a supernumerary tooth displaced into the infratemporal fossa during extraction - Alper Alkan; Nilay Er; Hakan Ocak; Türker Yücesoy (Istanbul University, 2018)
DOI: 10.26650/eor.2018.31977Accidental displacement of an impacted tooth into the infratemporal fossa (ITF) is a rare but serious complication because of the vulnerability of the surrounding anatomical structures. Here we present the case of a 40-year-old man who reported pain on the right side of his face. Panoramic radiography and cone-beam computed tomography revealed an impacted third molar and a supernumerary tooth positioned immediately below it. Under local anesthesia, the third molar was easily extracted; however, the supernumerary tooth was inadvertently displaced into the ITF. The position of the tooth was confirmed by radiographic examination, and it was immediately removed intraorally by expanding the flap and carefully dissecting the soft tissues. Clinical aspects of this rare complication were evaluated, with special emphasis on the reliability of imaging modalities and surgical techniques.